Phage therapy in the inactivation of A. hydrophila in bivalve molluscs - Duarte, João Pedro Macedo (2023)
The recurrent emergence of infections outbreaks associated with bivalve molluscs consumption is of extreme importance for public health. Aeromonas hydrophila is a human pathogen that is widely distributed in coastal areas, and is a causative agent of different diseases (e.g., gastroenteritis, wound infection, meningitis, endocarditis and septicaemia) in humans after consumption of contaminated seafood. Although bacterial elimination mostly depends on the depuration of bivalves, this process is not sufficiently safe and efficient to eliminate some microorganisms present in their tissues. The development and evaluation of new strategies with no adverse effects to bivalves, in order to reduce the concentration of potential human pathogens is therefore essential. One of the most promising approaches is to combine phage therapy with the depuration process. The use of bacteriophages (or phages) to control bacterial infections has been reported across numerous fields by many researchers. However, relatively the combination of depuration and phage therapy to eliminate pathogenic bacteria in bivalves there are only four studies, and these studies are restricted to three bacterial strains (Vibrio parahaemolyticus, Escherichia coli and Salmonella enterica serovar Typhimurium). Thus, the objective of this work was to evaluate the efficacy of three new phages to control A. hydrophila, in order to evaluate their potential application during depuration. Three new phages (AH-1, AH-4 and AH-5) were isolated and characterized in terms of host range, latent period, burst size, and development phage-resistant mutants. First, the phage-bacteria interaction was evaluated in vitro, using single suspensions of phages or phage cocktails. Time of treatment and the concentration of phage were also studied. The isolated phages, AH-1, AH-4 and AH-5, belonged to the Myoviridae family. In general, the increase of multiplicity of infection (MOI) from 1 to 1000 not promoted a significant increase in the efficiency of phage AH-1. The in vitro assays indicated that the use of phages AH-1, AH-4 and AH-5 can be an effective alternative to control of A. hydrophila, however, the phage AH-1 was the most efficient one (additional reduction of more 3 log CFU/mL) when compared with to the other two phages. The use of cocktails with two and three phages (AH-1/AH-4, AH-1/AH-5, AH4/AH-5 and AH-1/AH-4/AH-5) was lightly more effective (maximum reductions of 5.1-5.8 log CFU/mL) than the use of phages AH-4 and AH-5 alone (reductions of 4.9 and 4.5 log CFU/mL, respectively), however, the efficiency of phage AH-1 (maximum inactivation of 7.7 log CFU/mL) was significantly higher than the obtained with phage cocktails. Second, to confirm if the phage AH-1 can be used to control the A. hydrophila in bivalves, in vivo experiments, using artificially contaminated cockles were done. Depuration in static seawater at multiplicity of infection (MOI) of 1 with phage of AH-1 revealed a significantly decrease in the rate of A. hydrophila inactivation in cockles (1.0 log CFU/g) during treatment. Results indicated that combining phage biocontrol with depuration procedures enhance bivalve microbial safety for human consumption by improving decontamination efficiency, proving that this technology can be transposed to the bivalve industry.